Development of a core outcome set for pharmacological interventions in osteoporosis among patients with diabetes mellitus: an international consensus study protocol - Wei, Chao; Wang, Xiaobin; Mei, Zubing; Li, Jing (Frontiers in Pharmacology, 2025)
BackgroundOsteoporosis and diabetes mellitus (DM) are both prevalent chronic conditions associated with significant morbidity, particularly in aging populations. Patients with DM are at increased risk of developing osteoporosis due to complex pathophysiological interactions between glucose metabolism and bone health. Although pharmacological interventions have been used to prevent and manage osteoporosis in individuals with DM, variability in reported outcomes across studies hinders evidence synthesis and meta-analyses. A standardized Core Outcome Set (COS) is required to harmonize outcome reporting in clinical trials, improving comparability and clinical relevance. This paper outlines the protocol for developing a COS for pharmacological interventions targeting osteoporosis among patients with DM.MethodsThe development of the COS will follow a five-phase approach. Phase 1 involves a systematic review to identify key outcomes in clinical trials of osteoporosis pharmacotherapy in diabetic populations. Phase 2 consists of a modified Delphi process involving international experts in endocrinology, bone metabolism, and diabetes care, as well as patients and public representatives. This will be followed by Phase 3, where consensus meetings will be held to finalize the essential outcomes for inclusion. Phase 4 will focus on identifying appropriate outcome measurement tools based on a systematic review and additional consensus-building meetings. Finally, Phase 5 will involve dissemination and implementation activities to ensure broad adoption of the COS in future research and clinical trials. Patient and Public Involvement (PPI) will be integrated throughout all phases of the project to ensure the relevance of selected outcomes.ConclusionThe resulting COS will provide a standardized framework for reporting outcomes in pharmacological intervention studies of osteoporosis in patients with DM. By facilitating meta-analyses and data pooling, this COS will improve the comparability of clinical trials, enhance research efficiency, and reduce outcome reporting bias. Ultimately, the COS will support better clinical decision-making, fostering the development of targeted and effective therapies for osteoporosis in the context of diabetes.